2015
DOI: 10.1371/journal.pone.0133141
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Interaction with the MAGUK Protein Family Member, MPP1, via CRAC and CRAC-Like Motifs: An In Silico Docking Analysis

Abstract: Cholesterol is essential for the proper organization of the biological membrane. Therefore, predicting which proteins can bind cholesterol is important in understanding how proteins participate in lateral membrane organization. In this study, a simple bioinformatics approach was used to establish whether MPP1, a member of the MAGUK protein family, is capable of binding cholesterol. Modelled and experimentally-validated fragment structures were mined from online resources and searched for CRAC and CRAC-like mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Many cholesterol poses were predicted by the docking, with a wide range of interaction energies. However, it is well known that in the presence of strong hydrophobic interactions, as in the case of cholesterol, docking procedures are not always straightforward [45]. Therefore, only those poses which fulfill both higher scores (lower binding energy) and the vicinity to some CARC-CRAC motifs were shown in the figures (Figures 9b and c).…”
Section: In Silico Analysis Of the Interaction Of Octn1 With Cholesterolmentioning
confidence: 99%
“…Many cholesterol poses were predicted by the docking, with a wide range of interaction energies. However, it is well known that in the presence of strong hydrophobic interactions, as in the case of cholesterol, docking procedures are not always straightforward [45]. Therefore, only those poses which fulfill both higher scores (lower binding energy) and the vicinity to some CARC-CRAC motifs were shown in the figures (Figures 9b and c).…”
Section: In Silico Analysis Of the Interaction Of Octn1 With Cholesterolmentioning
confidence: 99%
“…The addition of MPP1 to the subphase underneath a monolayer of a lipid mixture without cholesterol induced a smaller change in the area at constant surface pressure, compared with that obtained for the same lipid mixture containing cholesterol. This decrease in area may indicate a structural modification, or molecular rearrangement, within the lipid monolayer that is specific to the type of monolayer composition, that is, either the MPP1 can bind directly to cholesterol, as shown by Listowski et al (2015) or that cholesterol modulates the arrangement of the lipid monolayer, i.e. inducing a phase separation (e.g.…”
Section: B a D C Ementioning
confidence: 99%
“…Our previous simple in silico modelling study on MPP1 (Listowski et al 2015) showed that this protein contains two hydrophobic/amphipathic stretches of ~12-18 amino acid residues which could be responsible for the binding or penetration of MPP1 to lipid bi-and mono-layers via hydrophobic interactions. The effect of ionic strength and pH would shed some light on this issue.…”
Section: B a D C Ementioning
confidence: 99%
“…We believe that flotillin-1 and -2 are important components of these nanoclusters, which was confirmed by the fact that flotillins are found in the DRM residual fraction even after treatment with beta methyl cyclodextrin. Binding of palmitoylated MPP1 to the pre-existing nanocomplexes via flotillins and perhaps via cholesterol-binding regions as was recently documented [75,[84][85][86] induces their fusion and stabilizes them as membrane resting-state rafts, which are larger (~20 nm) in diameter [90], more stable (~1 s), detergent-resistant, and which become functional (see Fig. 3).…”
Section: Mpp1 Is the Resting State Raft Organizing Protein In Erythromentioning
confidence: 80%
“…The obtained results show that MPP1 can bind cholesterol via CRAC and CRAC-like motifs with moderate to high affinity (K I in the nano-to micro-molar range). It was also found that palmitoylation-mimicking mutations (C/F or C/M) did not affect the affinity of MPP1 towards cholesterol [84]. Further studies on recombinant MPP1 interactions in simple Langmuir monolayer technique revealed that injection of MPP1 into the subphase of an LB monolayer composed of DOPC/SM/Chol (1:1:1 molar ratio) induced an increase in surface pressure, indicating that MPP1 molecules were incorporated into the lipid monolayer.…”
Section: Mpp1 Interacts With Cholesterol and Lipidsmentioning
confidence: 97%